Comparing the Efficacy of Gentamicin-heparin Solution to Heparin Alone as Catheter Related Blood Stream Infection in Patients Undergoing Hemodialysis. - Rafique, Kashif; Sabir, Omer; Riaz, Muhammad Mohsin; Rizvi, Nabiha; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Catheter Related Blood Stream Infection (CRBSI) using non tunnelled catheters is high. We performed a prospective randomized study to evaluate gentamicin catheter lock to prevent CRBSI. Methods: Hemodialysis patients initiating dialysis from the temporary jugular catheter between ages 18-80 were included. 100 each group of patients were randomized to A and B groups. patients randomized in two groups using a random numbers allocation table. GROUP A: After insertion the catheters of patients locked with a combination of Gentamicin (GENTICIN 5 mg/mL) 2 mL and Heparin 5000 Units (1 mL) according to the catheter volume (1.4 cc in venous port and 1.2 cc in arterial port). The catheters locked with the combination solution after each dialysis session. GROUP B: The catheters locked with Heparin 5000 units (1 mL) diluted in two mL normal saline. Catheters locked with heparin after all dialysis sessions until the end of study period. RESULTS Mean age was 50.06+12.09 in Grop A and 54.24+12.66 years in Group B, and 27(54%)were males. Comparison of efficacy of Gentamicin - Heparin solution to heparin alone as catheter lock for prevention of CRBSI shows that 6%(n=3) in Group-A and 28%(n=14) in Group-B developed CRBSI (p= 0.003) CONCLUSION The efficacy of gentamicin- heparin solution in preventing CRBSI is better than heparin alone when used as catheter lock solution in patients undergoing hemodialysis via temporary internal jugular catheter. A higher efficacy with gentamicin proves its usage as an effective and economical lock solution for prevention of CRBSI.